Potentially toxic cyanobacteria in Trentino lakes: bloom episodes detected by monitoring data over the last ten years - Sabrina Pozzi; Silvia Costaraoss; Giovanna Pellegrini (Advances in Oceanography and Limnology)
This short note illustrates some algal blooms caused by potentially toxic cyanobacteria in water bodies in the NE Alps, focusing in particular on the last ten years. The data illustrated come from monitoring activities, bathing health assessments, and analyses carried out on citizen reports. The most important blooms were caused by Planktothrix rubescens, Dolichospermum spp., and Microcystis aeruginosa, and affected Lakes Ledro, Caldonazzo, and Serraia. Experience in the Trentino region has highlighted the importance of effective and timely communication between the monitoring institutions and the users of the lake, to minimize any negative health effects and to increase the knowledge of the population.